Patients’ perceived needs of health care providers for low back pain management: a systematic scoping review - Chou, L.; Ranger, T.; Peiris, W.; Cicuttini, F.; Urquhart, D.; Sullivan, K.; Seneviwickrama, K.; Briggs, Andrew; Wluka, A. (Elsevier BV, 2018)
Background Context: Optimal management of low back pain (LBP) involves patients’ active participation in care, facilitated by positive interactions with their health care provider(s) (HCP). An understanding of patients’ perceived needs regarding their HCP is, therefore, necessary to achieve such outcomes. Therefore, the aim of the present study is to review the existing literature regarding patients’ perceived needs of HCP managing LBP. Methods: A systematic scoping review of publications in MEDLINE, EMBASE, CINAHL, and PsycINFO (1990–2016) was performed. Descriptive data regarding study design and methodology were extracted, and risk of bias was assessed. Aggregates of patients’ perceived needs of HCP for LBP were categorized. Results: Forty-three studies (30 qualitative, 12 quantitative, and 1 mixed methods) from 1,829 were relevant. Four areas of perceived need emerged: (1) there are several characteristics of HCP that patients desire, such as good communication and shared decision-making; (2) patients wanted HCP to provide information, including a cause of their LBP and legitimization of their symptoms; (3) patients’ valued holistic, individualized care, and continuity of care; and (4) patients perceived long waiting times, difficulties with access to treatment, cost, and personal effort to be obstacles to care. Conclusions: Patients with LBP want patient-centered care, to be actively involved, and they have identified characteristics of HCP that foster a good provider-patient relationship. They noted areas of dissatisfaction with HCP and perceived obstacles to care. Given limited health care resources, HCP and policy makers need to implement novel methods of health care delivery that address these issues to facilitate improved patient satisfaction and achieve better patient and health system outcomes.